PERANCANGAN ALAT BANTU ANGKAT JUMBO BAG PROSES MIXING PADA PT XYZ BATAM - Raja Doly Sirait; Sirait, Ganda (Computer Science and Industrial Engineering, 2025)
Labor is one of the most important assets for a company. However, human resources are not free from work-related issues. Ensuring comfort and safety at work can foster enthusiasm among employees. At PT XYZ BATAM, employees in the mixing department who manually and repeatedly pour materials have reported physical complaints. The aim of this study is to minimize the risk of musculoskeletal disorders (MSDs), identify the complaints experienced by workers, and design an ergonomic jumbo bag lifting aid to help improve poor working posture and enhance comfort. This research uses the Rapid Entire Body Assessment (REBA) method to analyze working posture and the Nordic Body Map (NBM) questionnaire to identify physical complaints. The Need, Idea, Decision, Action (NIDA) method is used to gather information needed by workers to reduce workplace issues and to develop new lifting aid designs based on previous tools. The results of the NBM questionnaire serve as the basis for the design process. The study found that workers experienced musculoskeletal complaints in the neck, back, waist, left thigh, right thigh, left knee, and right knee, with a moderate risk category. The most dominant complaint percentage reached 66.66%. As a solution, a jumbo bag lifting aid was designed with specifications of 100 cm in length, 100 cm in width, 120 cm in height, and a volume capacity of up to 1000 kg. This solution provides improved working comfort for employees.